Metal–Thiobenzoato Complexes: Synthesis, Structure, and Processing as Carbon‐Supported Nanoparticles. Issue 12 (25th March 2018) - Vallejo‐Sánchez, Daniel; Beobide, Garikoitz; Castillo, Oscar; Lanchas, Mónica; Luque, Antonio; Pérez‐Yáñez, Sonia; Román, Pascual
Abstract : Six new compounds of formula [M(TBn)2 L] [TBn: thiobenzoato; M: Pd II, Zn II, Cd II ; L: 2, 2′‐bipyridine (bpy), 1, 10‐phenanthroline (phen), 1, 2‐di‐(4‐pyridil)‐ethylene (bpe), neocuproine (neo), adenine (ade)] are obtained by the reaction of M(CH3 COO)2 · 2H2 O with thiobenzoic acid and N ‐heterocyclic ligands. The use of chelating ligands and adenine leads to monomeric compounds: [Pd(TBn)2 (bpy)] (PdBPY), [Pd(TBn)2 (phen)] (PdPHEN), [Zn(TBn)2 (neo)] (ZnNEO), [Cd(TBn)2 (neo)] (CdNEO), and [Cd(TBn)2 (ade)(CH3 OH)] (CdADE). In these compounds, the metal is bonded to the sulfur atoms of two TBn anions, while the remaining coordination positions are completed by the donor atoms of the ancillary ligands. The bridging capability of the bpe ligand gives rise to the polymeric [Cd(TBn)2 (µ‐bpe)] n (CdBPE) compound. The presence of direct sulfur–metal bonds and carbon‐rich coligands enables these complexes to yield, by means of a dry thermolysis process, a set of metallic and metal–sulfide nanoparticles embedded into a carbonaceous support. The process to produce the latter materials consists of aerobic thermolysis using moderate temperatures (300–500 °C) and short exposure times (minute scale). Analysis of the XRD patterns and SEM/TEM images reveals that the carbonaceous matrix hosts well‐dispersed nanocrystallites. The influence of the metal(II) atom, ancillary ligand, and thermal treatment parameters on the crystalline phase, size, and purity of the resulting carbon‐supported nanoparticles is discussed. Abstract : Six new air‐stable metal–thiobenzoato compounds with N ‐heterocycles have been synthesized and structurally characterized. Their solventless thermolysis, under aerobic conditions and at relatively mild temperatures (350–480 °C), provides, in a single step, carbon‐supported‐metal and metal–sulfide nanoparticles with high crystallinity.